DIVERSIFIKASI PRODUK DAN PEMANFAATAN VIRGIN COCONUT OIL DALAM BIDANG KESEHATAN PADA KELOMPOK WANITA TANI YAYASAN TAKSU TRIDATU - I Wayan Karta (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
The Taksu Tridatu Foundation's women's farmer group has a large coconut area, but the processing of coconut into an economic product has not been carried out, so training is needed to make VCO and its diversification. This is expected to improve the quality of health by utilizing VCO in therapeutic treatments and overcoming various diseases. Service methods carried out in community service activities are training and mentoring, making promotional media, tracking cooperation. The types of problems handled in this program include aspects of production and business management of VCO and their use in the health sector. The production aspect is by training women to produce VCO (manufacturing, quality control, diversification, packaging), while business management is carried out by collaborating with inns, restaurants, stalls, souvenir shops in Nusa Penida. The results of this activity include (1) female farmers have skills in making VCO and aromatherapy products of jasmin and sandalwood; (2) female farmers have the skills to process blondo waste into natural soap; (3) female farmers have activities to produce VCO and diversify them to be marketed or used for health; (4) The understanding of the fostered partners can be improved with the training that has been done.